Synthesis, Characterization and Thermal Studies of New Chelating Fulven Monomers, Polymers and Their Metal Complexes - SHAHADA, L.A.; AMIN, R.R. (Asian Journal of Chemistry, 2010)
The monomer exo-7-isopropylidenebicyclo[2,2,1]hept-2-ene-5,6-dicarboxylic acid anhydride (I) undergoes smooth ring-opening metathesis polymerization (ROMP) using the WCl6/(CH3)4Sn based catalyst to give the anhydride polymer (PI). Aiming to synthesize a chelating polymers, the monomer (I) was treated with potential complexing agent thiocarbohydrazide or oxalyldithiosemicarbazide to give exo-7 isopropylidenebicyclo[2,2,1]hept-2-ene-5,6-dicarboxylic acid amidothiocarbohydrazone and exo-7-isopropyli denebicyclo[2,2,1]-hept-2-ene-5,6-dicarboxylic acid amido oxalylthiosemicarbazone monomers (II) and (III), respectively. Unfortunately these two monomers are relatively inactive toward metathesis ring-opening polymerization using the WCl6/(CH3)4Sn based catalyst. It is already reported that the complex formation between chelating group namely S-methylhydrazinecarbodithioate and the WCl6 initiator completely inhibited the ROMP process. Therefore the synthesis of the desired chelating polymers (PII) and (PIII) were achieved by treating the anhydride precursor polymer (PI) with thiocarbohydrazide or oxalyldithiosemicarbazide, respectively. The current work also presents the synthesis and characterization of the metal complexes derived from monomers (II and III) and polymers (PII and PIII) with Cu(OAc)2.H2O, Co(OAc)2.4H2O and Ni(OAc)2.2H2O. The thermal analysis of the monomers, polymers and their metal complexes were studied by means of thermogravimetric analysis. The isolated complexes were formulated as [M2(II)(H2O)n].nH2O, [M2(III)(H2O)n], [M2(PII)(H2O)n].nH2O and [M2(PIII)(H2O)n] where M = Cu(II), Co(II) or Ni(II), n = 0-4 and (II), (III), (PII) and (PIII) are the chelating monomers and polymers used. The structures of polynuclear monomeric and polymeric thiosemicarbazones complexes are [Ni4(III)(OAcO)2(H2O)8].2H2O and [Cu4(PIII)(H2O)8].4H2O.